2019
DOI: 10.2196/14406
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Patients With Osteosarcoma in the European American Osteosarcoma Study-1 (EURAMOS-1): Development and Implementation of a Questionnaire Substudy

Abstract: BackgroundThe quality of life (QoL) of patients with osteosarcoma (OS) may be adversely affected by the disease or its treatment. Therefore, it is important to understand the QoL of patients undergoing treatment for OS to improve the QoL. We report on the first prospective international QoL study that was embedded within a large randomized clinical trial from 4 national study groups.ObjectiveThis paper aimed to describe the QoL study development, methodology, accrual details, and characteristics of the QoL coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…The histologic morphologies seen in our patient cohort also follow the expected distribution with the osteoblastic morphology (Fig. 1A,B) being the most common in 70.6% of patients [23]. Lastly, the outcomes in our patient cohort is consistent with literature, where we found that nearly 70% of patients had a favorable 5-year overall survival and patients with only localized disease had superior survival outcomes (p=0.0058) [12].…”
Section: Patient Informationsupporting
confidence: 87%
“…The histologic morphologies seen in our patient cohort also follow the expected distribution with the osteoblastic morphology (Fig. 1A,B) being the most common in 70.6% of patients [23]. Lastly, the outcomes in our patient cohort is consistent with literature, where we found that nearly 70% of patients had a favorable 5-year overall survival and patients with only localized disease had superior survival outcomes (p=0.0058) [12].…”
Section: Patient Informationsupporting
confidence: 87%
“…The overall study design [ 25 , 26 ] and the methodological specifics of the QoL questionnaire sub-study have been laid out in detail previously [ 27 ]. We briefly describe the study design.…”
Section: Methodsmentioning
confidence: 99%
“…The EURAMOS-1 trial cohort consisted of 2260 participants who, between the ages 5 and 40 years old, had been diagnosed with a previously untreated resectable high-grade osteosarcoma (at any site, except for craniofacial structures). Among these, 2213 participants were eligible for QoL-assessment (≥5 years old) and had a questionnaire in their respective language available (see [ 27 ]). Recruitment took place between 2005 and 2011, involving 17 countries and four study groups: the Children's Oncology Group (COG), the Cooperative Osteosarcoma Group (COSS), the European Osteosarcoma Intergroup (EOI), and the Scandinavian Sarcoma Group (SSG).…”
Section: Methodsmentioning
confidence: 99%
“…Negative occurrences such as nausea and vomiting, hepatotoxicity, anemia, neutropenia, and thrombocytopenia were discovered to be widespread in pediatric osteosarcoma patients enduring chemotherapy [13]. Factors linked with chemotherapy-induced liver toxicity comprised of increased chemotherapy quantities, elevated plasma methotrexate levels, and a more gradual pre-hydration velocity [31]. The quality of life of patients undergoing treatment for osteosarcoma was assessed in a prospective international study, which found that the disease itself and the treatment applied to the patients may negatively impact the patients quality of life [5].…”
Section: Discussionmentioning
confidence: 99%